Perception and product evaluation of selected Filipino teenagers toward online advertisements - Almario, Angelica C. (College of Home Economics, university of the Philippines Diliman, 2020)
The study describes how selected Filipino teenagers perceive online advertisements. It describes the meanings of advertisement elements and symbols as interpreted by these teenagers and how the overall perception of the advertisement relates to their product evaluation. In describing the phenomenon, the teenagers’ exposure to the Internet and online ads, their social environment, and the interpretation of an expert in communication research provide a backdrop to the study. This research focuses on 15 selected Filipino teenagers from Generation Z. It uses symbolic interactionism to emphasize the meanings and interpretations put into the online advertisements as perceived by the teenagers. The questionnaire used in this study consists of two parts. The first part was a survey questionnaire to explore the respondents’ Internet experiences; while the second part included questions for the one- on-one interview to test the respondents’ process of selection, organization, and interpretation of information in the five pre-selected online ads. In addition to that, this study tested the teenage consumers’ evaluations of the products presented in the ads. The results showed that Filipino teenagers have experience with both online advertisements and the Internet. The teens’ abilities to perceive information in ads are at par with the interviewed expert. The respondents were deemed skillful in trying to make sense of the symbols and elements presented in the ads and were able to interpret information in ads based from past experiences and knowledge. Moreover, this study found that there was only minimal relationship between perception and product evaluation. How teens see ads – whether acceptable or not – does not automatically mean that they are already decided to buy the endorsed products. To persuade teenage consumers, popular products or brands could benefit from the use of visuals and imagery in advertisements. However, to persuade teenage consumers to buy less popular products or brands, pertinent information about the product should be included in the ads instead.